The Influence Of Innovation Capacity And Training on The Performance of Full-Time Pppk Employees With Leadership Skills As an Intervening Variable Within The Banten Provincial Government - Ahmad Murtado; Ahmad Mukhlis; Angrian Permana (Economics and Digital Business Review, 2026)
The performance of Government Employees with Work Agreements (PPPK) is a crucial factor in supporting the effectiveness of government administration and public services. However, the performance of full-time PPPK within the Banten Provincial Government remains suboptimal, particularly in terms of timely completion of work and achievement of work targets. This situation is thought to be influenced by innovation capacity, training, and leadership skills. This study aims to analyze the effect of Innovation Capacity and Training on the Performance of Full-Time PPPK Employees within the Banten Provincial Government, with Leadership Skills as an intervening variable. The study used a quantitative approach using a survey method. The study population was 1,061 employees, with a sample of 250 respondents determined using proportional stratified random sampling. Data analysis was performed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software. The results of the study indicate that Innovation Capacity has a positive and significant effect on Employee Performance (β = 0.359; p < 0.05), Training (β = 0.217; p < 0.05), and Leadership Skills (β = 0.425; tp < 0.05). Furthermore, Leadership Skills have been shown to positively and significantly mediate the relationship between Innovation Capacity and Training on Employee Performance. The study concludes that continuously improving Innovation Capacity, Training, and Leadership Skills can improve the performance of Full-Time PPPK Employees in the Banten Provincial Government.